THE CONCEPT OF THE “HISTORICAL TIME” IN THE FRAME OF POST-NON-CLASSICAL SCIENCE - Svyatoslav RACHUK (Актуальні питання суспільних наук та історії медицини, 2020)
The purpose of the research is the philosophical and theoretical reflection of the concept of “historical time” through the prism of post-non-classical science. The determination of its proportionality with the definitions in the classical and non-classical era of scientific rationality. Theoretical substantiation from the position of a complex self-regulatory system and its axiological content. The relevance of the study: is due to the paradigmatic shift in the transition from non-classical to post-non-classical science, which led to a rethinking of the main theoretical concepts, in particular, historical science. For achieving this goal, there were used